Proceedings of the 4th International Conference on Foundations of Digital Games 2009
DOI: 10.1145/1536513.1536562
|View full text |Cite
|
Sign up to set email alerts
|

Creating a games class

Abstract: Adding a games class to a traditional computer science curriculum is becoming a popular way to attract and motivate students to consider computing. However, there are many decisions to be made when adding such a course to an existing Computer Science curriculum. What are the goals of the course? What platform and editor should be used? How should the course be administered? This paper gives a walkthrough of creating a games class that fits in a traditional curriculum, based on experience of creating the CSC 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Such concerns are further exacerbated by some common reasons given for the inception of games courses amongst established university programs. A growing mass of descriptive research has recently been published outlining the development of games-related courses which sit within the existing curricula of traditional computer science (CS) and engineering disciplines-see, for instance, Jones [2000], Burns [2008], Volk [2008], Zyda et al [2008], Coller and Scott [2009], and Duvall [2009]. However, the motive for the inclusion of games material in traditional study pathways is often reported to be that of stimulating interest in more traditional subject areas, particularly CS, which have experienced continued reductions in student numbers in recent years [Carter 2006;Defoe et al 2011;Estey et al 2009;Morrison and Preston 2009;Rocco and Yoder 2007]-a point which invariably fuels the concern among those in the games industry who reject the true validity of such courses.…”
Section: Introduction To Computer and Video Games Coursesmentioning
confidence: 99%
“…Such concerns are further exacerbated by some common reasons given for the inception of games courses amongst established university programs. A growing mass of descriptive research has recently been published outlining the development of games-related courses which sit within the existing curricula of traditional computer science (CS) and engineering disciplines-see, for instance, Jones [2000], Burns [2008], Volk [2008], Zyda et al [2008], Coller and Scott [2009], and Duvall [2009]. However, the motive for the inclusion of games material in traditional study pathways is often reported to be that of stimulating interest in more traditional subject areas, particularly CS, which have experienced continued reductions in student numbers in recent years [Carter 2006;Defoe et al 2011;Estey et al 2009;Morrison and Preston 2009;Rocco and Yoder 2007]-a point which invariably fuels the concern among those in the games industry who reject the true validity of such courses.…”
Section: Introduction To Computer and Video Games Coursesmentioning
confidence: 99%
“…Certain education methodologies such as team-working [1,2,3,4] or studio-based learning [5] have been applied to these courses. Other methodologies such as interdisciplinary collaboration have also been applied [7,8,9].…”
Section: Introductionmentioning
confidence: 99%